Microbiological analyses of poultry litter used for ruminant feeding - SchockenIturrino, R. P.; Sampaio, AAM; Sampaio, MAPM; Berchieri, A.; Berchielli, SCP (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1996)
The aims of this study were to estimate the changes in total bacterial counts (TBC) in poultry litter samples, consisting of rice hulls, after storage, and to identify pathogenic bacteria. For the countings Plate Count agar (Difco) was used. Enrichment and selective media such as blood agar, MacConkey, Baird Parker, brain and heart agar, and egg yolk solid media, and cooked meat and brain and heart infusion, incubated under aerobic or anaerobic conditions were used to isolate Staphylococcus aureus, Salmonella sp, Clostridium perfringens, C. botulinum, C. chauvoei, Campylobacter sp, Escherichia coli, and Corynebacterium sp. Litter samples were collected from the houses of the Veterinary School experimental aviary. A fully randomized experimental design was used with four treatments and four replications, for a total of 16 samples. A decrease in TBC was detected when treatment T1 (zero days of storage) was compared with treatments T2 (14 days of storage). on the other hand the treatments T3 (28 days of storage) and T4 (42 days of storage) presented significantly superior counting in relation to treatment T1. Some pathogenic bacteria of Enterobacteriaceae such as Escherichia coil, Proteus, Arizona, Providencia, Edwardsiella, as well as Staphylococcus aureus, S. epidermidis, different species of genus Clostridium as C. perfringens, C. sordelli, C. chauvoei, C. tetani and C. novyi as well as some strains of Corynebacterium pyogenes were isolated.
Keywords: microbiological analyses; poultry litter; ruminant feeding